A Review of the Clinical Use of Ultrasound in Korean Traditional Medicine - Seok Hee Kim; Tae Han Yook; Beom Yong Song; Yoo Min Choi; Jin Hyeon Shin; Hye Jeong Shin; Sanghun Lee; Young Ju Jeon; Jong Uk Kim (MEDrang Inc., 2019)
This study was performed to evaluate research studies utilizing ultrasound diagnostic units, the practitioners who performed the ultrasound assessments, and how they had been used primarily in tandem with the Korean Medicine Advanced Searching Integrated System. This study identified 46 studies following a literature search, and discovered that a Korean medicine doctor led the ultrasonography in 13 studies, a medical technician was responsible in 6 studies, a roentgenologist carried it out in 5, and 19 of the studies did not specify who had conducted it. Ultrasonography had been actively used in the course of the clinical practice of Korean medicine, and it may serve as a useful and reliable diagnostic tool for evaluating the effectiveness of Korean medicine. The results of this study will help to promote more ultrasound studies in the future.